2020
DOI: 10.32479/ijeep.9180
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Natural Resources, Renewable Energy, Economic Growth on Carbon Dioxide Emission in Malaysia

Abstract: The purpose of this article is to analyze the impact of natural resources, renewable energy, and economic growth on carbon dioxide (CO 2 ) emission in Malaysia. Due to the increase in industrialization the state of Malaysia faces significant problems such as environmental pollution. In this study time series data has been used and the ARIMA equation has been used by the researcher in this study. The researcher collected the data from the year 1988 to 2017. The outcomes of the study suggest that natural resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 30 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…Also, enhancing economic development can control pollution levels. Likewise (Aeknarajindawat et al, 2020), found that green energy utilization curbs emissions in Malaysia. However, enhancing development levels intensify emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, enhancing economic development can control pollution levels. Likewise (Aeknarajindawat et al, 2020), found that green energy utilization curbs emissions in Malaysia. However, enhancing development levels intensify emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…De Bruyn et al (1998) also provide evidence of the existence of the EKC hypothesis for the Netherlands, the UK, the USA, and Western Germany, and Galeotti and Lanza (1999) do so for 110 countries. More recently, several studies used more complex statistical methods to test the EKC hypothesis without finding qualitatively different results (Halkos and Tsionas, 2001;Bertinelli and Strobl, 2004;Martinez-Zarzoso and Bengochea-Morancho, 2004;Bradford et al, 2005;Liu, 2005;Vollebergh et al, 2005;Galeotti et al, 2006;Song et al, 2008;Fodha and Zaghdoud, 2010;Shahbaz et al, 2013;Bassetti et al, 2013;Aeknarajindawat, Suteerachai and Suksod, 2020;Bekun, Agboola and Joshua, 2020;Rana and Sharma, 2019;Rauf et al, 2018;Wasti andZaidi, 2020 andZambrano-Monserrate et al, 2016). On the other hand, several studies find limited evidence of the presence of EKC for CO 2 emissions (e.g., Dinda, 2004;Tol et al, 2009;He and Rickard, 2010;Wang et al, 2011;Adedoyin, Awosusi and Adeshola, 2020;Dogan and Inglesi-Lotz, 2020;Koc and Bulus, 2020;Mikayilov, Galeotti and Hasanov, 2018;Sarkodie, 2018 andWang et al, 2019).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Despite the growing number of studies, the seemingly scarce of study for the case of Ghana and African countries on the current issue (Gyamfi, 2021;Joshua and Bekun, 2020) compared to studies on other developing and developed countries/regions regarding natural resources and carbon emission (Aeknarajindawat et al, 2020;Khan et al, 2020Khan et al, , 2021Balsalobre-Lorente et al, 2018;Agboola et al, 2021) and debt and carbon dioxide emission (Bese et al, 2021;Zhao and Liu, 2022) necessitate further studies. Also, the potential non-linear relationship between debt and carbon emission has not been examined empirically yet.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the growing number of studies, the seemingly scarce of study for the case of Ghana and African countries on the current issue (Gyamfi, 2021; Kwakwa et al. , 2020; Joshua and Bekun, 2020) compared to studies on other developing and developed countries/regions regarding natural resources and carbon emission (Aeknarajindawat et al. , 2020; Khan et al.…”
Section: Introductionmentioning
confidence: 99%